Analisis Implementasi Kebijakan Sertifikasi Guru dalam Meningkatkan Kompetensi Guru SMP Negeri di Kecamatan Jatiwangi - Susi Susilawati; Ipik Permana; Moh Taufik Hidayat (Universitas Swadaya Gunung Jati, 2014)
ABSTRACT This research is a descriptive qualitative or using verbal data from respondent information about the certification policy implementation analysis to improve the competence of teachers in junior high school teachers in the district Jatiwangi. Key informants in this study are the Head of the District Education Office Majalengka, Head of Civil Service District Education Office Majalengka, and supporter informant was Staff Officer Majalengka District Education Office and Teachers Participant Teacher Certification. Data collection techniques that are used ie Library Studies and Field Studies. This study uses the theory of Van Metter implements and Horn. In theory, the success of policy implementation is influenced by six factors: the size and purpose of the policy, resources, characteristics of the implementing agency, attitude/ tendency (disposition) the executor, the executor of communication between organizations and activities, and the economic environment, social, and political. Furthermore, to analyze the implementation of teacher certification policies to improve the competence of teachers Junior High School in District Jatiwangi, this research will focus on observing such factors as the phenomenon of observations.Based on the results of the study showed that the implementation of teacher certification policies to improve the competence of teachers Junior High School in District Jatiwangi already well underway. However, there are still some obstacles. Barriers such as lack of clarity of the information received by teachers as teacher certification participants, this obscurity in the form of lack of clear information on the requirements and certify the first step, a lack of infrastructure to support certification requirements, such as the lack of space for storing files certification participants, the lack of incentives for employees who take care of the activities of participants of certification that there is still budget manipulation. District Education Office needs to conduct socialization Majalengka better to teacher certification participants by empowering school principals and school coordinators for the utilization or use of the database in order to process the certification submission can run effectively and efficiently.